THE PROCESS OF FORMULATING OFFICIAL CATHOLIC TEACHINGS: CONSULTING THE LAITY AND SENSUS FIDELIUM - Tirimanna, Vimal (Asian Horizons, 2015)
Traditionally, Christian theology has upheld the fact that all the baptized are anointed by the Holy Spirit, and consequently, the Christian community as a whole will not be allowed to fall into error by the same Spirit, with regard to its faith and morals. Vatican II officially resurrected this traditional belief in and through the concept of sensus fidelium as expressed explicitly in LG, 12. However, during the post- Vatican II era what the concept implies with regard to the process of official Church teaching, namely, to consult all the baptized (majority of whom are the laity) has not happened, resulting in a glaring gap between the teachings of the clerical hierarchy and the rest of the Church. The article, while insisting that majority or public opinion cannot be equated to sensus fidelium, nevertheless, points out the indispensable need to consult and listen to the laity if the Church’s teaching is to be credible in the eyes of the contemporary believers.